2011
DOI: 10.1111/j.1742-7843.2011.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Doxorubicin and Fenofibrate on the Activities of NADH Oxidase and Citrate Synthase in Mice

Abstract: Doxorubicin (Dox) has widely been used as an anticancer drug, but its use is limited by serious toxicity to the heart, kidney and liver. Mitochondrial dysfunction is one of the potential mechanisms of toxicity but not fully understood. Fenofibrate, one of the peroxisome proliferator-activated receptor-alpha (PPARa) ligands, is involved in lipid metabolism which takes place primarily in the mitochondria, so mitochondrial function may be affected by fenofibrate. Therefore, we investigated the effects of DOX and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Because fenofibrate can affect cardiac mitochondrial respiration [2830], we next investigated mitochondria number and ultrastructure in MuRF1−/− hearts after fenofibrate treatment (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Because fenofibrate can affect cardiac mitochondrial respiration [2830], we next investigated mitochondria number and ultrastructure in MuRF1−/− hearts after fenofibrate treatment (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Our starting hypothesis was based on DOX effects on respiratory complexes and mitochondrial carriers (Cheneval et al, 1983;Davies and Doroshow, 1986;Nicolay and de Kruijff, 1987;Oliveira and Wallace, 2006;Yao et al, 2011). We had anticipated that OXPHOS enzymatic reserves were lower in the heart or, alternatively, that OXPHOS in heart mitochondria was dependent in one particular respiratory complex, more so than liver or kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DOX has been reported to interfere with Complex III and IV (Nicolay and de Kruijff, 1987), the phosphate carrier (Cheneval et al, 1983) and the adenine nucleotide translocator (ANT) (Oliveira and Wallace, 2006), among other mitochondrial proteins. Although most of the studies report effects in heart or cardiac-like models, some of DOX effects are shared among other tissues (Nicolay and de Kruijff, 1987;Santos et al, 2002;Yao et al, 2011). Still, DOX-induced toxicity preferentially occurs in the heart.…”
Section: Introductionmentioning
confidence: 99%
“…One of the well-known mechanisms of Dox is the inhibition of macromolecular biosynthesis by DNA intercalation (Momparler et al, 1976) as well as its cytotoxic action is manifested by the inhibition of topoisomerse II (Bodley et al, 1989). Also, few earlier reported studies demonstrated the role of Dox in escalating free radical production which leads to cytotoxicity in various organs like heart, brain, liver, and kidney (Tacar et al, 2013;Yao et al, 2011). In the current study, we evaluated the potential effect of NR to ameliorate the Dox-induced acute cardiac toxicity in rats.…”
Section: Discussionmentioning
confidence: 99%